Middle Eocene Nannofossil Assemblages Responding to Depositional Dynamics of the Elat Formation, Maluku - Ratih C. F. Ratumanan; Vijaya Isnaniawardhani; Budi Muljana (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
The Kei Besar Island is mainly composed of the Elat Formation carbonate rocks. This research was conducted to determine the nannofossils assemblages in the Elat Formation to interpret the depositional dynamics during its formation. Lithological observations and sampling for nannofossil analysis were carried out on three measured stratigraphic sections: Section 1 - Hollat, Section 2 - Ngurdu, and Section 3 - Mata Hollat. A total of 47 species assigned to 25 genera of nannofossils were identified in 45 selected samples. The succession of the Elat Formation in the study area formed at NP16 to N17 or Middle Eocene. Stratigraphic reconstruction supported by biostratigraphy analysis shows that Section 3 at the lower (NP16 to NP 17), Section 2 in the middle part (NP 17), and Section 1 at the upper (NP 17). R-mode cluster analysis of nannofossils defined four species clusters (assemblies A, B, C and D) that tend to occur together. Q-mode cluster analysis defined five depth-distribution clusters (1, 2, 3, 4, and 5), each deposited under similar conditions. Based on large foraminifera, the succession was formed in fore reef setting in neritic bathymetric zone. Coarsening and thickening upward supported by the nannofossil assemblages indicate depositional dynamics which tend to be shallower. Reworked fossils, commonly found at the lower of the Elat Formation, show the mechanism of turbid currents in early deposition.